SAFETY PROCEDURE USED IN INDUSTRIAL ELECTRIC MAINTENANCE: hazardous energy blocking (LOTO) - Barrena Potto, Cleverson Paulo; Rodolpho, Daniela (Revista Interface Tecnológica, 2021)
The objective of this article is to present a lotto locking and tagging system (Lockout and Tagout), whose main objective is to guarantee the absence of potential energy contained in sources that produce or store energy such as in tanks, pipes, frames power lines, electrical distribution networks, operating machines. Such locking and tagging and / or signaling devices provide protection and safety for workers, preventing machines or equipment in operations from unexpectedly energizing or releasing stored energy, causing severe or fatal work accidents to employees. Through studies and bibliographic research, it is possible to design safe procedures for blocking and signaling equipment during service and maintenance operations. Specifying which steps employees must follow to prevent accidents associated with dangerous energies, ensuring the physical integrity of the workers involved in the activity.
Keywords: Safety.; Lotus.; Signaling.; Procedure.